1973
DOI: 10.1111/j.1365-2389.1973.tb00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Btpyridylium Herbicides With Organo‐clay Complex

Abstract: The adsorption of diquat (r,i'-ethylene-z,z'-bipyridylium dibromide) and paraquat (I, i'-dimethyl-4,+'-dipyridylium dichloride) by an organo-clay complex has been investigated. Paraquat was adsorbed by the organo-clay complex in greater amounts than was diquat. Infrared studies suggest the formation of charge-transfer complexes between diquat or paraquat and the organo-clay complex. Organic matter upon interaction with clay may facilitate the adsorption of diquat and paraquat on clay minerals in soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…We determined the simple correlations between the Kf and Downloaded by [York University Libraries] at 18:27 19 November 2014 Kd OM-ODTMA /Kfd OM ratio, suggest that this pesticide is adsorbed by clay-humus complexes formed in the soil. Different authors have reported that when these complexes are present in soils containing montmorillonite, they enhance the sorbent power of the clay and that of the OM (Khan, 1973;Sánchez-Camazano and Sánchez-Martín, 1990).…”
Section: Resultsmentioning
confidence: 98%
“…We determined the simple correlations between the Kf and Downloaded by [York University Libraries] at 18:27 19 November 2014 Kd OM-ODTMA /Kfd OM ratio, suggest that this pesticide is adsorbed by clay-humus complexes formed in the soil. Different authors have reported that when these complexes are present in soils containing montmorillonite, they enhance the sorbent power of the clay and that of the OM (Khan, 1973;Sánchez-Camazano and Sánchez-Martín, 1990).…”
Section: Resultsmentioning
confidence: 98%
“…Reduced mobility and biocidal activity due to bonding to humic substances are often described (5)(6)(7)(8). It is in some cases supported by various experimental results, that parent molecules or metabolites are bound to the humic matrix either by covalent bonding (9)(10)(11)(12)(13)(14)(15)(16)51), ionic bonding (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), charge transfer complexes (29)(30)(31)(32)(33), ligand exchange (34,35), hydrogen bonding (23,31,(36)(37)(38)(39)(40), van der Waals forces (22,(41)(42)(43)(44), hydrophobic sorption (45)(46)(47)(48)(49)…”
Section: Comission On Pesticide Chemistrymentioning
confidence: 88%
“…Such an association may facilitate adsorption of pesticides by inorganic constituents (Khan, 1973). Therefore, it is the combined inorganic-organic colloid interaction that needs to be evaluated in determining the full magnitude of pesticide adsorption capacity by colloids (Saltzman et al, 1972).…”
Section: Introductionmentioning
confidence: 99%